A phase I, randomized, placebo‐controlled trial to evaluate the pharmacokinetics, safety, and tolerability of nirsevimab in healthy Chinese adults - Xiaomeng Mao; Xiaohan Hua; Chengyi Wu; Xiaoyun Ge; Jie Zhang; Xiaojie Wu; Robert J. Kubiak; Ulrika Wählby Hamrén; Tonya Villafana; Georgios Christou; Jannine Green; Therese Takas; et al. (Clinical and Translational Science)
Abstract Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infection (LRTI) in infants worldwide. Nirsevimab, an extended half‐life monoclonal antibody against RSV, is approved in China for the prevention of RSV lower respiratory tract disease in infants; however, global nirsevimab trials did not enroll Chinese infants. To inform the investigation of nirsevimab for the prevention of RSV LRTI in Chinese infants, this Phase I, randomized, placebo‐controlled trial evaluated the pharmacokinetics (PK) and safety of nirsevimab in healthy Chinese adults. Participants were randomized 3:1 to a single 300 mg intramuscular dose of nirsevimab or placebo and were followed through 150 days post‐dose. Serum nirsevimab concentrations were measured and PK parameters of maximum serum concentration (Cmax), time to maximum concentration (tmax), and area under the concentration‐time curve from time 0 to Day 150 (AUC0–150) were estimated. Treatment emergent adverse events (AEs), clinical laboratory data, and vital signs were evaluated. Overall, 24 participants were randomized to nirsevimab (n = 18) or placebo (n = 6). Nirsevimab geometric mean (coefficient of variation [%CV]) Cmax was 46.9 (21.7) μg/mL, median (range) tmax was 7.0 (4.9, 29.9) days, and geometric mean (%CV) AUC0–150 was 4210.6 (13.6) μg·day/mL. Treatment‐emergent AEs (all Grade 1 or Grade 2 in severity) were reported in 5/18 (27.8%) nirsevimab recipients and 2/6 (33.3%) placebo recipients. No serious AEs, new onset chronic disease, or deaths were reported. Overall, safety and PK outcomes were consistent with those observed in healthy adults in the USA, with no new safety concerns.